(3GdeSGFds - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s ((3Ydi Hf MSf Hf eMeO GdMQGfi s)
(3ChdgG (B:s
(3eSCdI SFd YfgG SjOfG GHf JjejI ajef bGd Cf fTHg GdHGQi GdYdh ef LejY GdLgGJ GdeNdhbI s
(3BNQgG (B:s
(3fLRJ GdeSGFd HMeO Gddg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: 7s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds